Functions of Music in Film : The Meeting of Visual and Aural Arts - Hery - Supiarza (Cinematology: Journal Anthology of Film and Television Studies, 2022)
This research describes the meeting between visual and aural arts in film. Does the meeting affect all aspects of the psychology of the audience. Music as an aural art gives a feeling of being alive in the body of the audience. When a viewer feels horror when watching a horror film, when the audience feels a heroic feeling when seeing a patriotic scene, it is interesting to study how music plays a major role in expressing visuals and influencing the audience. The categories of diagetic and non-diagetic sounds in films are sounds that the audience sometimes doesn't realize that they have a big influence on the psychology of the audience. The question that needs to be answered is the meeting between visual and aural art in the film, why does it have an impact. A qualitative method with a literature study approach was carried out to obtain data in answering research questions. Through literature study of various scientific writings, data were collected to find out the truth. This study found that music has an important role to enter into the world of film. Music has a function in integrating the audience's subconscious in seeing images. Music enters the audience's feelings which then gives an influence on behavior as a result of the audience's own knowledge of the music they listen to. Music influences the audience more in terms of expression. The results of this study can be used as a reference for further research to explore the various influences of music in films for various disciplines. It is also important for filmmakers to consider story narratives as the main reference for incorporating music into films.